Rancang Bangun Wireless Analog To Digital Data Logger Berbasis Arduino Uno dengan Media Bluetooth dan Android - effendi, effendi; Fakhruddin; M. Ilyas Fadilla (Politeknik Aceh, 2025)
This Wireless Analog to Digital Data Logger research aims to design a prototype measuring tool that is useful for converting analog data into digital data, or an Analog to Digital Converter (ADC), without using cable media (wireless), where the communication media used in this research is Bluetooth by using the HC-05 module and Arduino Uno as the main control system. The system output of the measurement results in this research is displayed on the Android phone in the form of decimal numbers to make it easier to read, along with the date, month, and year, as well as the time when the measurement was taken. This system is also equipped with a graphic display of measurement results in real time, making it easier for users to monitor changes in data that occur visually. This measuring tool also has a facility for storing measurement data in the form of an Excel file with CSV (comma separated values) format, which can be downloaded from the data storage media on the Android phone used, making it easier for users to process or retrace the measurement data on other media such as computers.